2018
DOI: 10.1371/journal.pone.0202361
|View full text |Cite
|
Sign up to set email alerts
|

Predicting acute renal failure in Bothrops snakebite patients in a tertiary reference center, Western Brazilian Amazon

Abstract: Acute Kidney Injury (AKI) is the main systemic complication and cause of death in viperid envenomation. Although there are hypotheses for the development of AKI, the mechanisms involved are still not established. The aim of this study was to evaluate the clinical-laboratorial-epidemiological factors associated with AKI in victims of Bothrops sp envenomation. This is an observational study carried out at the Fundação de Medicina Tropical Dr. Heitor Vieira Dourado. AKI was defined according to the guidelines of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 48 publications
3
48
0
Order By: Relevance
“…The main involved organisms were Aeromonas hydrophila, Morganella morganii , and Bacteroides sp. These data are in concordance with the published literature [ 12 , 13 ].…”
Section: Discussionsupporting
confidence: 93%
“…The main involved organisms were Aeromonas hydrophila, Morganella morganii , and Bacteroides sp. These data are in concordance with the published literature [ 12 , 13 ].…”
Section: Discussionsupporting
confidence: 93%
“…In Brazil, Costa Rica and Panama, antivenoms are freely available for patients in all reference hospitals and health centers [61], which is an effective measure to decrease mortality. Moreover, studies have suggested a delayed time between snakebite and antivenom administration in patients with higher incidence of AKI, therefore it is important to observe the antivenom distribution chain [5,66].…”
Section: Mortality Due To Bothrops Envenomingmentioning
confidence: 99%
“…However, only a few applied the AKI definition according to KDIGO, AKIN or RIFLE criteria [5,8,11,14,56,[67][68][69][70][71][72][73][74]. Data from retrospective series described a great variable in AKI incidence, 1.4 to 44.4% [5,8,11,56,[66][67][68][69][70][71][72][73][74]. Therefore, the real incidence of AKI due to Bothrops envenoming is underestimated, not only because of the ambiguity of the definition, but also the absence of notification in some rural areas [63] (Table 1).…”
Section: Incidence Of Aki Following Bothrops Envenomingmentioning
confidence: 99%
“…The venom has proteins capable of breaking the integrity of the vascular endothelium. The union of hemorrhagic action and coagulation disorders can cause detectable bleeds, such as bleeding gums, blood in the urine and hemorrhagic stroke, as well as other potentially lifethreatening complications [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Acute renal injury is the most common systemic complication and the leading cause of death from Viperidae poisoning [10]. Involvement of the liver by the venom of the bothropic species has also been associated with complications such as the formation of a subcapsular hematoma [15].…”
Section: Case Reportmentioning
confidence: 99%